1996
DOI: 10.1074/jbc.271.52.33550
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Carcinogenic Chromium(VI)-induced DNA-Protein Cross-linking and Their Characterization in Cultured Intact Human Cells

Abstract: DNA-protein complexes (DPCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 55 publications
3
30
0
Order By: Relevance
“…The decreased ability of the cell to repair DNA damage sustained during the replication process, could be the result of Cr(III) ion mediated inhibition of synthesome associated DNA polymerase δ and ε activity within the cell. In support of this suggestion, Cr(VI)-induced formation of binary Cr-DNA or DNA-DNA cross-links, and ternary Cr-DNA-protein complexes was shown to correlate with a metal ion induced increase in DNA damage (Mattagajasingh and Misra, 1996). Thus, the decrease in the activity and fidelity with which the DNA synthesome mediates DNA replication in the presence of Cr(III) ion, could be the result of the DNA synthesome forming DNA-protein-chromium complexes at these higher concentrations of Cr(III) ion.…”
Section: Discussionmentioning
confidence: 82%
“…The decreased ability of the cell to repair DNA damage sustained during the replication process, could be the result of Cr(III) ion mediated inhibition of synthesome associated DNA polymerase δ and ε activity within the cell. In support of this suggestion, Cr(VI)-induced formation of binary Cr-DNA or DNA-DNA cross-links, and ternary Cr-DNA-protein complexes was shown to correlate with a metal ion induced increase in DNA damage (Mattagajasingh and Misra, 1996). Thus, the decrease in the activity and fidelity with which the DNA synthesome mediates DNA replication in the presence of Cr(III) ion, could be the result of the DNA synthesome forming DNA-protein-chromium complexes at these higher concentrations of Cr(III) ion.…”
Section: Discussionmentioning
confidence: 82%
“…23,24 In addition, Cr(VI)/Cr(III) redox cycling produces ROS, which can contribute to the formation of DPCs by the free radical mechanism shown in Figure 2A. 25 …”
Section: Introductionmentioning
confidence: 99%
“…However, in earlier studies we have demonstrated that only about 19% of Cr(VI)-induced DPCs could be disrupted by EDTA-chelation and the remaining 81% require nuclease digestion (Mattagajasingh andMisra, 1996, 1999). Furthermore, we and others have also demonstrated that Cr(VI) treatment produces an 'oxidative stress' in cells and increases the cellular level of prooxidants (Mattagajasingh andMisra, 1995a, 1997;Travacio et al, 2001;Goulart et al, 2005;Kalahasthi et al, 2006;Fatima and Mahmood, 2007), and the majority of DPCs could be suppressed with antioxidant pretreatment (Mattagajasingh and Misra, 1996).…”
Section: Introductionmentioning
confidence: 94%
“…Cr(VI) is known to induce a variety of DNA lesions, including oxidation of DNA bases, single-and double-strand DNA breaks, and DNA-DNA and DNA-protein crosslinks (Wedrychowski et al, 1985;Mattagajasingh et al, 1996). Because Cr(VI) does not bind to DNA or proteins in cell-free systems (Fornace et al, 1981), but Cr(III) does (Cohen et al, 1990), some of the Cr(VI)-induced DNA-protein crosslinks (DPCs) could be disrupted by EDTA (Miller and Costa, 1989;Mattagajasingh andMisra, 1995b, 1996), a chelator of Cr(III) but not Cr(VI), and it is known that Cr(III) can induce DNA-amino acid crosslinks (Salnikov et al, 1992), it has been generally believed that a biologically reduced form of Cr(VI) such as Cr(III) physically mediates DNA-protein crosslinking.…”
Section: Introductionmentioning
confidence: 99%